Nosocomial Infection Outbreak with Enterobacter aerogenes at a Neonatal Intensive Care Unit and Its Outcomes - Ulubaş Işık, Dilek; Bas, Ahmet Yagmur; Kulali, Ferit; Ozcan, Beyza; Unal, Sezin; Yucel, Husniye; Demirel, Nihal (Journal of Pediatric Infectious Diseases, 2019)
Objective Health care associated infections (HAIs) in the neonatal intensive care unit (NICU) are a significant cause of neonatal morbidity and mortality. Enterobacter aerogenes, a gram-negative bacterium, rarely causes HAI in the pediatric and NICUs. We report the case of a HAI outbreak of E. aerogenes in an NICU and discuss the clinical spectrum and outcome of the affected preterm newborns and successful prevention measures.Materials and Methods A retrospective study was conducted in a level III NICU of Etlik Zubeyde Hanım Women's Health Teaching and Research Hospital. The infants with blood cultures positive for E. aerogenes during the outbreak were enrolled. Perinatal risk factors, laboratory findings, symptoms, treatment, and prognosis were recorded. Clinical applications and prevention measures were identified.Results A preterm infant of 27 weeks of gestation who was diagnosed on the eighth postnatal day was the initial case of the reported outbreak of health care associated E. aerogenes infection. Subsequently, 12 more infants were diagnosed in the next 3 months. Infants' mean gestational age was 27.1 ± 2.3 weeks, and mean birthweight was 902 ± 161 g. The clinical symptoms at presentation were respiratory distress, sclerema, circulatory failure, and shock, which appeared at a mean age of 7.6 ± 5.8 days. Analysis of E. aerogenes strains revealed that all strains were of the same clonal type. Eight patients died in follow-up due to E. aerogenes septicemia during this outbreak. The mean interval between the onset of symptoms and death was 1.5 ± 1 days.Conclusion Outbreaks of health care associated E. aerogenes infection result in a high mortality rate among very low birthweight infants. Awareness of adjustable risk factors and preventive measures to control the outbreak decreases both morbidity and mortality.
Keywords: Enterobacter aerogenes; neonate; outcome